2012
DOI: 10.1002/cd.20005
|View full text |Cite
|
Sign up to set email alerts
|

Guided cognitive reframing of adolescent-father conflict: Who Mexican American and European American adolescents seek and why

Abstract: Adolescents may seek to understand family conflict by seeking out confidants. However, little is known about whom adolescents seek, whether and how such support helps youth, and the factors that predict which sources are sought. This chapter offers a conceptual model of guided cognitive reframing that emphasizes the behavioral, cognitive, and affective implications of confidant support as well as individual, family, and cultural factors linked to support seeking. We present empirical data from 392 families of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…However, we found limited evidence for this conclusion in the present work, because ethnicity accounted for very few differential associations. Additionally, in an earlier paper, we did not find evidence that cultural values predicted whether fathers were sought out to discuss the father–child relationship (Cookston et al., ), suggesting that the expression of respect may not result in differential guided cognitive reframing processes for adolescents of Mexican American and European ancestry.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…However, we found limited evidence for this conclusion in the present work, because ethnicity accounted for very few differential associations. Additionally, in an earlier paper, we did not find evidence that cultural values predicted whether fathers were sought out to discuss the father–child relationship (Cookston et al., ), suggesting that the expression of respect may not result in differential guided cognitive reframing processes for adolescents of Mexican American and European ancestry.…”
Section: Discussioncontrasting
confidence: 63%
“…Specifically, how much adolescents believe they matter to their co‐residential fathers and stepfathers explains problem behaviors such as depressive symptoms and externalizing behaviors, exclusive of how much they believe they matter to their mothers. In an earlier investigation (Cookston et al., ), we found that whether the co‐residential father was a biological father or a stepfather was not associated with whether children sought him out for guided cognitive reframing. However, because the current study is focused on what happens after the child seeks out the co‐residential father/stepfather for conversation, we will test whether guided cognitive reframing operates differently for the two father types.…”
Section: A Focus On the Co‐residential Father/stepfather–child Relatimentioning
confidence: 53%
See 2 more Smart Citations
“…The significance of parent nurture as a determinant of how children will adapt to the parental separation transition has gained a lot of research attention (e.g. Adamsons & Johnson, 2013;Fabricius et al, 2012;Kelly & Emery, 2003;Robinson, 2006). Robinson (2006) states that warm and nurturing relationships with parents buffer the effects of adversity by providing a secure base in the continued development of child wellbeing, although child wellbeing has been empirically linked to relationships with both parents post separation (e.g.…”
Section: The Parent-child Relationshipmentioning
confidence: 99%